PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN KFC ALAM SUTERA - Fitriyani, Fitriyani Fitriyani; Atmojo, Kunto; Basir, Abdul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This study aims to determine the effect of Work Motivation on Employee Performance at KFC Alam Sutera. The method used is simple linear regression with a quantitative approach, involving a sample of 35 respondents from KFC Alam Sutera employees. The results show that Work Motivation has a significant effect on Employee Performance, with a t-value of 5.328 and a significance level of < 0.001. The F-test indicates that the model is statistically significant overall (F = 28.388; Sig < 0.001). The R Square value of 0.462 indicates that 46.2% of the variation in employee performance is explained by work motivation. Keywords: Work Motivation, Employee Performance, Simple Linear Regression